2019
DOI: 10.11130/jei.2019.34.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Impact of Trade Openness on Informal and Irregular Employment in Egypt

Abstract: This study examines the impact of trade openness on job quality, measured by the share of informal and irregular employment in total employment. By combining a microeconomic dataset (the Egyptian Labor Market Panel Survey) with macroeconomic variables (tariffs), we assess the effect of trade reforms on informal/irregular workers in Egypt. Our main findings show that there is a positive association between tariffs and both informal and irregular employments in Egypt. This effect is likely because the least prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Note however that several caveats can apply. First, despite the fact that our results hold across several specifications (including IV) and although trade liberalizations in Egypt followed the indications of international institutions and were implemented similarly across sectors, which should reduce the possibility of endogeneity (Salem and Zaki 2019), a strict causal interpretation is probably still not warranted at this stage, also due to data limitations. Moreover, our sample covers only part of the economy, i.e.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Note however that several caveats can apply. First, despite the fact that our results hold across several specifications (including IV) and although trade liberalizations in Egypt followed the indications of international institutions and were implemented similarly across sectors, which should reduce the possibility of endogeneity (Salem and Zaki 2019), a strict causal interpretation is probably still not warranted at this stage, also due to data limitations. Moreover, our sample covers only part of the economy, i.e.…”
Section: Resultsmentioning
confidence: 85%
“…Yet, in the case of Egypt there are several elements suggesting that trade policy reforms are likely to be driven by external factors. First, as mentioned in the first part of the paper, the liberalization waves essentially followed the indications of the international institutions as the World Bank and the International Monetary Fund (first) and the WTO (later), or a countrywide attempt to internationalize the economy, thus making tariffs in Egypt “less likely to be endogenous than those in other countries” (Salem and Zaki 2019 ). Second, and consistently with the previous point, tariff trends were very similar across industries as shown by the correlations in Table 1 , and this co-movements of tariffs, in turn, suggests an absence of interference or lobbying from the private sector (see Erten et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an empirical approach, many papers show that trade liberalisation decreases informality: Aleman‐Castilla (2006) shows empirically that import tariff elimination in Mexico following NAFTA led to the reduction of the likelihood of informality in the tradable sectors. Selwaness and Zaki (2015) found that trade liberalisation has reduced informality in Egypt's manufacturing sector; Salem and Zaki (2019) found that there is a positive association between tariffs and both informal and irregular employment in Egypt; Huynh et al. (2020) prove that FDI inflows help reduce shadow economy (informal economy); and Canh & Dinh Thanh, 2020 prove that export diversification and quality can reduce shadow economy when moving beyond a tipping point.…”
Section: Introductionmentioning
confidence: 99%